2003
DOI: 10.1121/1.1610452
|View full text |Cite
|
Sign up to set email alerts
|

Forward masking in different cochlear implant systems

Abstract: The goal of this study was to evaluate, from a psychophysical standpoint, the neural spread of excitation produced by the stimulation of different types of intracochlear electrode arrays: the Ineraid, the Clarion S-Series on its own or with the Electrode Positioning System (EPS), and the Clarion HiFocus-I with the EPS. The EPS is an independent silicone part designed to bring the electrode array close to the modiolus. Forward masking was evaluated in 12 adult subjects (3 Ineraid, 4 Clarion S-Series, 3 Clarion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
57
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 22 publications
8
57
0
Order By: Relevance
“…They showed that for four out of six subjects, the stimulation of the two most apical electrodes did not produce the perception of pitch differences. Boëx et al (2003) reported the case of one Clarion S-series listener, implanted with a positioner (Fayad et al 2003) who improved his consonant identification performance when his deepest apical electrodes (above 532-) were deactivated. This subject showed also important neural interactions on these apical electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that for four out of six subjects, the stimulation of the two most apical electrodes did not produce the perception of pitch differences. Boëx et al (2003) reported the case of one Clarion S-series listener, implanted with a positioner (Fayad et al 2003) who improved his consonant identification performance when his deepest apical electrodes (above 532-) were deactivated. This subject showed also important neural interactions on these apical electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between spectral components have been well documented in studies presenting sounds simultaneously or successively (e,g., Moore, 2002;Oxenham & Shera, 2003). Likewise in electrical hearing, channel interactions have been observed in response to both simultaneous and nonsimultaneous pulse trains, the former presumably governed by the summation of current in the cochlea (Bierer 2007;de Balthasar et al, 2003;Stickney et al, 2006) and the latter by forward-masking effects in the auditory nerve and central pathways (Bierer & Faulkner, 2010;Boëx et al, 2003;Chatterjee et al, 2006;Kwon & van den Honert, 2006;Nelson et al, 2008). As in acoustic hearing, some degree of channel interaction is expected and probably desirable for discriminating complex sounds.…”
Section: Current Flow and Channel Interactionmentioning
confidence: 99%
“…The larger number of active neurons would likely result in a louder percept than in Figure 1A, but it also causes partial overlap of the two neural populations. The excitation of common neural elements with dual-channel stimulation can ultimately affect perception of the separate stimulus components, a phenomenon referred to as channel interaction (Bierer, 2007;Bierer & Faulkner, 2010;Boëx, Kos, & Pelizzone, 2003;Chatterjee et al, 2006;de Balthasar et al, 2003;Kwon & van den Honert, 2006;McKay et al, 1996;Nelson et al, 2008;Stickney et al, 2006). Acoustic stimulation is generally "multichannel" in the sense that different frequency components, having different time-varying amplitudes, can fall within the passband of the same neuron.…”
Section: Current Flow and Channel Interactionmentioning
confidence: 99%
“…However these psychophysical studies also reported large variability across subjects. Some subjects exhibited forward masking patterns with a pronounced peak in a 1-2 mm region around the probe, while others had masking excitation patterns that had a broad peak extending over 8 mm or more (Boex et al, 2003;Shannon, 1998, 2006;Kwon and van den Honert, 2006a).…”
Section: Evidence Of Focusing With Bipolar and Tripolar Stimulationsmentioning
confidence: 99%
“…In general, bipolar maskers have not demonstrated narrower forward masking patterns than monopolar maskers (Boex et al, 2003;Kwon and van den Honert, 2006a;Shannon, 1983). Kwon and van den Honert (2006a) directly compared bipolar (BP + 1 and BP + 2) and monopolar configurations in four subjects.…”
Section: Evidence Of Focusing With Bipolar and Tripolar Stimulationsmentioning
confidence: 99%